2016
DOI: 10.4018/ijehmc.2016040103
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Large Scale Implementation of Personalized Medicine in the Current Scenario

Abstract: Personalized Medicine (PM) is an emerging concept in the modern healthcare system and can play a vital role in modern healthcare management. If this concept can be adopted and implemented in a proper manner, the entire healthcare system will attain an elevated dimension. However, there exist many difficulties in adopting personalized healthcare system. An attempt has been made in this paper to present the data obtained through survey that has been conducted amongst a group of medical practitioners and a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Alharbi et al assessed the knowledge of 126 South Arabian physicians about PM in diabetes mellitus management and found that 82.5% of the participants had poor knowledge in this area [ 82 ]. These and other studies [ 37 , 44 47 , 58 , 86 , 105 108 ] reveal the need for further education of many health care providers, however, this requirement may vary between professionals in different fields [ 53 , 81 ]. An exception seems to be the skills of physicians in oncology.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Alharbi et al assessed the knowledge of 126 South Arabian physicians about PM in diabetes mellitus management and found that 82.5% of the participants had poor knowledge in this area [ 82 ]. These and other studies [ 37 , 44 47 , 58 , 86 , 105 108 ] reveal the need for further education of many health care providers, however, this requirement may vary between professionals in different fields [ 53 , 81 ]. An exception seems to be the skills of physicians in oncology.…”
Section: Resultsmentioning
confidence: 98%
“…A survey of medical practitioners and patients in India gives a somewhat more optimistic impression. Some of the respondents believe that data confidentiality is secured by advances in technology, while others are suspicious of whether the person entrusted with confidentiality can guarantee data security [ 105 ]. However, it seems that the human factor is the greatest weakness of the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all the benefits of cloud‐based services, the rate of its adoption in the healthcare sector is not as expected. Several authors and cloud experts have stated that the primary concerns inhibiting cloud adoption in healthcare sector have been privacy concerns , , , , , . These concerns make patients and medical workers worry about the usage of cloud‐based healthcare services as they fear the loss of their private data , .…”
Section: Background and Motivationmentioning
confidence: 99%
“…In the same scholarly article, the authors have dwelt on a number of issues that offer hindrance to the implementation of this scientific mode of clinical treatment. Misra and Bisui (2015) have also researched the feasibility of Personalized Medicine adoption. They have shown that in the given scenario it is quite difficult to adopt Personalized Medicine successfully.…”
Section: Background and Motivationmentioning
confidence: 99%